2022
DOI: 10.1037/spy0000286
|View full text |Cite
|
Sign up to set email alerts
|

The effect of implicit learning on motor performance under psychological pressure: A systematic review and meta-analysis.

Abstract: Motor skills learned implicitly should be less susceptible to deterioration under psychological pressure (i.e., choking) than skills learned more explicitly. In this systematic review and meta-analysis, we investigated that prediction. A systematic search was conducted for articles that had participants learn a motor skill implicitly relative to a comparison group and had both groups perform the skill under low-and high-pressure conditions. Ten studies with a median of nine participants/group met inclusion cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 56 publications
(153 reference statements)
1
18
0
Order By: Relevance
“…According to Liabo et al (2017), to assess the quality of eligible articles, it is important to consider (a) the relevance of each article's topic to the research question, (b) the appropriateness of the study type to the research question, and (c) the soundness of the study methods. Given that there have been several articles questioning the methodological practices in implicit-learning research, Cabral et al (2022) needed to carefully evaluate the methodological soundness of the included articles. As concerns relating to comparison groups represent a broader issue for sport psychology and motor learning research as well (see Bobrownicki et al, 2021), such advice would apply more generally too.…”
Section: Assessment Of Bias and Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…According to Liabo et al (2017), to assess the quality of eligible articles, it is important to consider (a) the relevance of each article's topic to the research question, (b) the appropriateness of the study type to the research question, and (c) the soundness of the study methods. Given that there have been several articles questioning the methodological practices in implicit-learning research, Cabral et al (2022) needed to carefully evaluate the methodological soundness of the included articles. As concerns relating to comparison groups represent a broader issue for sport psychology and motor learning research as well (see Bobrownicki et al, 2021), such advice would apply more generally too.…”
Section: Assessment Of Bias and Qualitymentioning
confidence: 99%
“…In addition to these concerns regarding population and intervention, we contend that the development of PICO(T)-informed objectives would also have assisted Cabral et al (2022) in recognizing and accounting for critical issues and debates in the implicit-learning literature relating to comparison groups. Although unacknowledged in Cabral et al’s systematic review, there exist several significant methodological issues concerning comparison groups that have been (a) explicitly laid out and debated in the implicit-learning literature (e.g., comparison groups are typically provided instructions of much greater quantity, lesser quality, and different meaning; Bobrownicki et al, 2018), (b) demonstrated empirically (Bobrownicki et al, 2015), and (c) proposed as likely explanations for the previously inconsistent findings (Bobrownicki et al, 2019).…”
Section: Research Question and Study Objectivesmentioning
confidence: 99%
See 3 more Smart Citations